Insights into Sustainable Food Systems: Learnings from Odisha’s Agricultural Officers - Junuthula, Shirisha; Kumari, Veenita (Journal of Agricultural Extension Management, 2025)
Sustainable food systems stand as pivotal pillars in addressing global food security challenges, emphasizing the need for environmentally conscious agricultural practices. Within this context, this research study delves into the realm of sustainable food systems, focusing on the invaluable insights gleaned from the dedicated cadre of Odisha’s Agricultural Officers. Their profound expertise and hands-on experience in agriculture form the bedrock of this investigation, offering a comprehensive understanding of sustainable agricultural practices and their implementation within the unique landscape of Odisha. The primary goal of this study is to unravel the intricate tapestry of sustainable agricultural practices through the lens of these proficient Agricultural Officers. Their perceptions, attitudes, and knowledge pertaining to crucial facets of sustainable agriculture-ranging from soil health, water management, integrated pest management, to organic farming and more-serve as fundamental keystones in this exploration. Through a structured methodology that involved pre-assessment questionnaires, exposure to sustainable agriculture concepts, and subsequent postassessment evaluations, this research uncovers the transformative learnings and evolving perspectives of these esteemed officers. Their wealth of experience and nuanced understanding of sustainable agricultural principles and challenges significantly contributes to the broader discourse on achieving agricultural sustainability. By delving into the unique insights and experiences of Odisha’s Agricultural Officers, this study aspires to shed light on actionable strategies and potential pathways to foster sustainable food systems. Ultimately, these findings not only enrich the understanding of sustainable agriculture but also hold the promise of guiding future towards a more sustainable and resilient agricultural landscape in Odisha and beyond